The Effect of Study Habits and Creative Thinking Disposition on Mathematical Creative Thinking Skills - Nur Isrotun Nafisatulina; Lilik Ariyanto; Irkham Ulil Albab (EduMa: Mathematics education learning and teaching, 2024)
This study aims to determine the effect of study habits and creative thinking disposition on mathematical creative thinking skill. The research method uses quantitative method. The population in this study is all of the seventh-grade students at Darul Ulum Gombong Junior High School in the odd semester of the 2022/2023 academic year totaling 57 students. The data collection technique used in this research are the test of mathematical creative thinking skill, study habits questionnaire and creative thinking disposition questionnaire. Data analysis techniques with analysis multiple regression. The results of this research are that there is a positive and significant effect between study habits and creative thinking dispositions on mathematical creative thinking skills.